Baicalein and Berberine Inhibit the Growth and Virulence of Clostridioides difficile - Xue Yang; Dongming Zheng; Jiangyan Yong; Yuchen Li; Yunzhi Sun; Fei Zhao; Daiyan Tang; Yi Xie; Dongming Bi (Pathogens)
Clostridioides difficile is a leading pathogen involved in healthcare-associated diarrhea. With its increasing incidence, mortality, and antibiotic resistance, there is an urgent need for novel therapeutic strategies to address the infection and prevent its recurrence. Gegen Qinlian Decoction (GQD) is a traditional Chinese medicine for the treatment of diarrhea, but its main active ingredient is not known. Therefore, in this study, we evaluated the biological activity of berberine (BER) and baicalein (BAI), key components of GQD, against C. difficile. Time–kill curves and scanning electron microscopy were employed to assess their effects on C. difficile growth, while Enzyme-Linked Immunosorbnent Assay (ELISA) and cytotoxicity assays were used to examine their impact on toxin production. We also employed Quantitative Reverse Transcription PCR (qRT-PCR) to examine how BER and BAI influenced the expression of toxin-associated genes. At sub-inhibitory concentrations, these compounds exerted antibacterial activity against C. difficile by disrupting the integrity of the cell membrane and cell wall. Furthermore, BER and BAI also suppressed toxin production, demonstrating effects comparable to those of vancomycin. This suppression likely resulted from their bactericidal activity and the inhibition of toxin gene expression. This study not only highlights the potential application of GQD in treating C. difficile infections but also offers promising options for developing drugs targeting the growth and virulence of this pathogen. C. difficile infection (CDI) is a leading cause of severe diarrhea, and its treatment remains challenging due to limited drug options and its high recurrence rate. BAI and BER, the main active components of the traditional Chinese medicinal formula GQD, inhibited the growth of C. difficile by disrupting its cellular structure and significantly reduced the production of toxins associated with disease severity. Furthermore, the effects of BAI and BER on C. difficile were comparable to those of conventional antibiotics, suggesting that these compounds could be potential alternative therapies for CDI. This study not only highlights the therapeutic potential of GQD in treating CDI but also provides a replicable research strategy for the development of novel anti-CDI agents.